2013
DOI: 10.1002/jsfa.6309
|View full text |Cite
|
Sign up to set email alerts
|

Optimized expression, purification and characterization of a family 11 xylanase (AuXyn11A) from Aspergillus usamii E001 in Pichia pastoris

Abstract: Its high specific activity and good enzymatic properties suggest that reAuXyn11A is a potential candidate for applications in industrial processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, the pH condition is also an important factor for optimizing the expression of yeast recombinant proteins . It was reported that lowering the pH during the production stage generally mitigated protease activity and improved product quality . However, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the pH condition is also an important factor for optimizing the expression of yeast recombinant proteins . It was reported that lowering the pH during the production stage generally mitigated protease activity and improved product quality . However, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 It was reported that lowering the pH during the production stage generally mitigated protease activity and improved product quality. 28 However, Fig. 2C shows that a relatively high pH value of 6.5 was the most suitable pH condition for IFTase expression by GS115-IFTase.…”
Section: Effect Of Culture Conditions On Recombinant Iftase Productionmentioning
confidence: 90%
“…The activities of recombinant SyS1 and SyGDH expressed in two recombinant E. coli strains were assayed and compared. Finally, the reaction conditions for asymmetric reduction of m-CPC to (R)-CCE catalyzed by whole E. coli/Sygdh-Sys1 cells were optimized using a 'one-parameter-at-a-time' method (Zhang et al 2014). To our knowledge, this is the first report on the asymmetric reduction of m-CPC coupled with regeneration of NADPH in situ by recombinant E. coli cells co-expressing both SyS1 and SyGDH.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, an endo- β -1,4-xylanase with high specific activity and good enzymatic properties was isolated from A. usamii . Furthermore, the gene encoding endo- β -1,4-xylanase from A. usamii was cloned and expressed in P. pastoris [ 9 , 10 ]. However, the low expression level does not allow the recombinant xylanase to be applied practically and economically in industry.…”
Section: Introductionmentioning
confidence: 99%